Approach to documentary production on solidarity organizations in the southern provinces of Santander - Cáceres Gómez, Luz Stella; Ramírez Garzón , María Teresa; Gutiérrez Sánchez, Hernando Alexander (Cooperativismo & Desarrollo, 2020)
This study aims to compile the documentary production published between 1981 and 2018 about the solidarity organizations of the southern provinces of Santander. With a qualitative approach, we reviewed 73 documents from different organizations at a national level. Furthermore, we prepared a specialized analytical summary for each document, and information was organized in an Excel matrix so that the writings could be made visible by periods and, therefore, historically identify the documentary material’s behavior. This article shows results organized by epoch and asserts that the publications were given individually and collectively in the three stages. Between 1981 and 1999, 13 publications were registered; between 2000 and 2009, 31, and from 2010 to 2018, 29. The authors identified in the study published mainly in the journals Cuadernos de Desarrollo Rural and Unisangil Empresarial. It is highlighted that the topics that attract the most attention from the authors are savings and credit cooperatives, those that focus on the agricultural and agro-industrial sector, and tourism. Among the main findings are the contributions referred to the success registered in the cooperatives, achieved through organizational innovation, greater autonomy, and the associates’ empowerment. The policies established in the Santander region on cooperatives and other economic organizations have considered it an example for other Colombian regions.